Implications for health system reform, workforce recovery and rebuilding in the context of the Great Recession and COVID-19: a case study of workforce trends in Ireland 2008-2021 - Padraic Fleming; Steve Thomas; Des Williams; Jack Kennedy; Sara Burke (BMC, 2022)
Abstract Background Workforce is a fundamental health systems building block, with unprecedented measures taken to meet extra demand and facilitate surge capacity during the COVID-19 pandemic, following a prolonged period of austerity. This case study examines trends in Ireland's publicly funded health service workforce, from the global financial crisis, through the Recovery period and into the COVID-19 pandemic, to understand resource allocation across community and acute settings. Specifically, this paper aims to uncover whether skill-mix and staff capacity are aligned with policy intent and the broader reform agenda to achieve universal access to integrated healthcare, in part, by shifting free care into primary and community settings. Methods Secondary analysis of anonymised aggregated national human resources data was conducted over a period of almost 14 years, from December 31st 2008 to August 31st 2021. Comparative analysis was conducted, by professional cadre, across three keys periods: 'Recession period' December 31st 2008-December 31st 2014; 'Recovery period' December 31st 2014-December 31st 2019; and the 'COVID-19 period' December 31st 2019-August 31st 2021. Results During the Recession period there was an overall decrease of 8.1% (n = 9333) between December 31st 2008 and December 31st 2014, while the Recovery period saw the overall staff levels rebound and increase by 15.2% (n = 16,789) between December 31st 2014 and December 31st 2019. These figures continued to grow, at an accelerated rate during the most recent COVID-19 period, increasing by a further 8.9% (n = 10,716) in under 2 years. However, a notable shift occurred in 2013, when the number of staff in acute services surpassed those employed in community services (n = 50,038 and 49,857, respectively). This gap accelerated during the Recovery and COVID-19 phase. By August 2021, there were 13,645 more whole-time equivalents in acute settings compared to community, a complete reverse of the 2008 situation. This was consistent across all cadres. Workforce absence trends indicate short-term spikes resulting from shocks while COVID-19 redeployment disproportionately impacted negatively on primary care and community services. Conclusions This paper clearly demonstrates the prioritisation of staff recruitment within acute services-increasing needed capacity, without the same commitment to support government policy to shift care into primary and community settings. Concerted action including the permanent redistribution of personnel is required to ensure progressive and sustainable responses are learned from recent shocks.